Perancangan Multimedia Interaktif Tentang Kesenian Jaranan Turangga Yaksa Sebagai Media Pembelajaran Di SDN 3 Pringapus Kabupaten Trenggalek - abdulloh eizzi irsyada; nerin sulistiani; faldi hendrawan (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2018)
Understanding of regional culture needs to be owned by everyone from an early age. At SDN 3 Pringapus studied the art of jaranan Turangga Yaksa to introduce his students. But the learning process is only fixed on the book and the lack of interactive factors, so that students' interest in learning decreases. With the development of information technology, efforts to increase children's learning interest can be done with various media, one of which is using interactive media. Therefore designed an interactive multimedia using multimedia processing software. The character used is the character of the child complete with jaranan clothes with a cheerful face, the dominant color is green, and the basic colors and text are simple so that it is easy to read to understand the material conveyed by students. After the process is complete, then testing the effectiveness of the product by distributing questionnaires. The results obtained in the study through the distribution of questionnaires that have been conducted at SDN III Pringapus in Dongko sub-district, Trenggalek district, can be concluded that 93% of the learning media are said to be effective.